Reduced Expression of RBP7 is Associated with Resistance to Tamoxifen In Luminal A Breast Cancer - Yan, Xiaolu; Gao, Zhe; Zhang, Lixia; Chen, Chuan (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Background: Tamoxifen is the most commonly used hormonal treatment for ERα-positive breast cancer. Tamoxifen resistance is still a big problem for ERα target therapy. RBP7 is a member of the cellular retinol-binding protein family. Objective: This study aims to investigate the prognostic role of RBP7 and the relationship between RBP7 expression and sensitivity or resistance to tamoxifen in ERα-positive breast cancer. Methods: A bioinformatics method was used to investigate RBP7 expression and the prognostic value of RBP7 in different subtypes of breast cancer. The relationship between RBP7 expression and sensitivity or resistance to tamoxifen was studied using clinical data (GSE1379) and cell line data (GSE27473, GSE2645923, GSM3715281, and GSM3715282). Transfection of RBP7 experiments was used to testify to the function of RBP7 in MCF7 cell. Results: RBP7 is a member of the family of cellular retinol-binding proteins. RBP7 expression was down-regulated at both mRNA and protein levels in breast cancer and was not associated with different TNM (Tumor, Node, Metastasis) stages. High expression of RBP7 was significantly related to good relative percent survival in the luminal A subtype, but in negative breast cancer, the result was opposite. The ROC plot showed that RBP7 had a significant predictive value for the tamoxifen response in the luminal A subtype. The expression of RBP7 from patients with recurrence treated with tamoxifen was significantly reduced. Gene Expression Omnibus showed that RBP7 expression was reduced considerably in tamoxifen-resistant MCF7 cells and T47D cells. The expression of RBP7 was positively correlated with some microRNAs involved in negatively regulating tamoxifen-resistant breast cancer. We also found that the expression of RBP7 decreased significantly in tamoxifen-resistant MCF7 cells, and transfection of RBP7 increased the sensitivity of resistant cells to tamoxifen. Conclusion: Reduced expression of RBP7 is associated with resistance to tamoxifen in luminal A breast cancer. Our research may help to explore the mechanisms of resistance of breast cancer to tamoxifen.
Keywords: tamoxifen